PENGGUNAAN MEDIA INTERAKTIF BAAMBOOZLE PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SMP NEGERI 24 MALANG - Rizkyta Amalinda (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This article describes the use of Bamboozle in learning Social Sciences. The research approach uses a qualitative approach with data in the form of words. Library research is carried out by collecting data and information from library sources, such as articles, books, journals, document, and other library sources. The results of the study show that web-based media on Bamboozle include providing independent learning opportunities, making questions by creating an account on Bamboozle for free, and how to play Bamboozle on Social Sciences material. The disadvantages of Bamboozle include very limited features, the creation of a question maker account and answering questions are not distinguished, there is no access permission to start the game, the game can only be played per team, there are no instruments on Bamboozle, only the back sound when selecting the answer, at the time using media makes it possible for passive students While the advantage of Bamboozle is to access Bamboozle without having to create an account, there are various questions, and it can be used for each level of education. Bamboozle can be accessed via a laptop or handphone